APPLICATION OF THE COX METHOD TO DIGITAL IMAGES FOR COPYRIGHT PROTECTION - Abdul Sani Sembiring; Pandi Barita Nauli Simangunsong (INFOKUM, 2022)
All these digital products can be downloaded easily. And can be exchanged with services such as e-mail. One way to protect multimedia copyrights is to embed information into the multimedia data (watermarking) as a digital signature of the legal owner of the multimedia product. Thus, the embedded watermark does not damage the protected digital data. So that the person who opens the multimedia product knows about the ownership of the maker. Digital data that will be applied in this research is only data in the form of digital images. Currently there are several watermarking methods that can be applied to digital images, such as: Least Significant Bit Coding, Patchwork (introduced by Bender), Pitas and Kaskalis, Caroni, Cox, Randomly Sequenced Pulse Position Modulated Code (RSPPMC), and others. However, the authors are interested in methods that utilize the characteristics of the Discrete Cosine Transform (DCT).